2020
DOI: 10.1371/journal.pone.0233604
|View full text |Cite
|
Sign up to set email alerts
|

Public oral health services performance in Brazil: Influence of the work process and service structure

Abstract: The quality of oral health care might be evaluated based on Donabedian's structure-process-outcome model. This study assessed the association between the oral health public services structure and work process of oral health teams (OHT) and performance indicators (access and problem-solving capacity) in Brazil. Secondary data from a national program obtained through interviews and by observation in 2013/2014 were analyzed. The performance indicators were Coverage of First Scheduled Dental Appointment (FDA) (< o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
2
9
0
1
Order By: Relevance
“…The findings showed that users were satisfied with the services in the presence of better conditions of the structure, considering the availability of a greater amount of equipment and items of ambience. Although oral health service is not restricted to the structural component, several studies have demonstrated a positive relationship among the amount of equipment, the dental appointments provided and the problem‐solving capacity of the CEO 21,29,30 . As previously observed, in this study, user satisfaction was associated with the existence of a higher number of items of equipment in conditions of use in CEOs, 31 which was similar regarding the presence of items of ambience that constituted safe and welcoming spaces 5,29,32 .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The findings showed that users were satisfied with the services in the presence of better conditions of the structure, considering the availability of a greater amount of equipment and items of ambience. Although oral health service is not restricted to the structural component, several studies have demonstrated a positive relationship among the amount of equipment, the dental appointments provided and the problem‐solving capacity of the CEO 21,29,30 . As previously observed, in this study, user satisfaction was associated with the existence of a higher number of items of equipment in conditions of use in CEOs, 31 which was similar regarding the presence of items of ambience that constituted safe and welcoming spaces 5,29,32 .…”
Section: Discussionsupporting
confidence: 81%
“…Although oral health service is not restricted to the structural component, several studies have demonstrated a positive relationship among the amount of equipment, the dental appointments provided and the problem-solving capacity of the CEO. 21,29,30 As previously observed, in this study, user satisfaction was associated with the existence of a higher number of items of equipment in conditions of use in CEOs, 31 which was similar regarding the presence of items of ambience that constituted safe and welcoming spaces. 5,29,32 Environments with these characteristics can favour the relationships between professionals and users, making health care more welcoming, resolutive and human.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…For the structure of the health units, variables were selected that reflected elements of human resources, physical structure and organizational structure [ 17 , 33 , 34 ]. For the work process, variables related to the organization of the agenda were selected in order to allow access to the first consultation and the continuity of treatment [ 35 37 ], as well as the provision of various health services in the dental office and at home [ 38 , 39 ].…”
Section: Methodsmentioning
confidence: 99%